Assess the Effectiveness of Peppermint Water on Nipple Crack Among Post Natal Mothers in Saveetha Medical College and Hospital, Thandalam - Prof. Dr. S. KalaBarathi (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Nipple damage in breastfeeding mothers are common causes of premature breast feeding cessation. Sore nipple associated with breast feeding are common problems with an incidence ranging from 11% to 96% and may leads to premature weaning. This frequency occurs from suction trauma to the nipple secondary to incorrect positioning at the breast. Nipple crack (nipple trauma) is a condition that can occur in breasting women as a result of a number of possible causes and incorrect attachment to the breast and healing may be difficult because of repeated trauma from the infant’s sucking. so the present study is done to assess the effectiveness of peppermint water on nipple crack among postnatal mother Saveetha college of nursing. Quantitative approach descriptive design was adapted to conduct this study.60 sample were selected this study (30 experimental group and 30 control group). The data was collected using the nipple trauma checklist after application of nipple crack in experimental group to assess the effect of peppermint water on nipple crack among postnatal mother. Result is Out of 30 sample in the experimental group is mother have 24 (80%) no crack, 4 (13.333%) mild crack, 2 (6.67%) moderate crack. out of 30 In control group mother have (0%), no crack, (0%) mild crack, 20(66.67%) moderate crack, 10 (33.33%) severe crack. conclusion of the study peppermint water reduction of nipple crack among postnatal mother.